Effects of Calcium- and Seaweed-Based Biostimulants on Sweet Cherry Profitability and Quality - Marlene Santos; Carolina Maia; Inês Meireles; Sandra Pereira; Marcos Egea-Cortines; João Ricardo Sousa; Fernando Raimundo; Manuela Matos; Berta Gonçalves (Biology and Life Sciences Forum, 2024)
Sweet cherry trees are one of the most important crops worldwide, producing fruits with high economic importance due to the nutritional value and bioactive properties of cherries, providing benefits to human health. Due to the currently unstable climatic conditions, cherry cracking has become a significant problem, strongly affecting the quality and yield of cherry orchards. A cracking rate of 20–25% at harvest can render cherry production unprofitable, decreasing the commercial value of the fruit, as only the cracked ones can be sold to processing industries. This study aims to assess the impact of calcium- and seaweed-based biostimulant applications on sweet cherry quality and profitability in cv. Sweetheart. Applying 300 g hL−1 of calcium led to a significant 52% reduction in the cracking index and a substantial 136% increase in orchard yield. Similarly, applying 150 mL hL−1 of seaweed resulted in a 2% increase in fruit weight and a 3% decrease in the cracking index. Therefore, our findings suggest that calcium- and seaweed-based biostimulants could serve as novel and sustainable alternatives for orchard producers, enhancing cherry profitability and marketability.